Methods of processing green, yellow and black gaharu tea: article - Shuhaimi, Muhammad Asyraf; Alwi, Habsah (2019)
Aquilaria tea also known as Gaharu tea in Malaysia is made from the leaves of aquilaria a protected tree species of the tropicla forest. The popular plantation species are Aquilaria crassna, A. malaccensis and A.sinensis. Currently, there is no formal method in processing gaharu tea in the market. Compared to tea derived from the leaves of Camillia sinensis the standard tea in the market, there are three type of tea that can be produced through different processing method mainly by the degree of fermentation from each type of tea which result in green tea, yellow tea and black tea. The objective of this study is to perform processing method of green tea, yellow tea and black tea on gaharu leaves and to analyse the chemical constituents which is caffeine and antioxidant. To analyse caffeine, elemental analyzer was used to determine the composition of nitrogen because molecular structure of caffeine is composed mainly of nitrogen atoms. Based on the result obtained, the nitrogen composition is the highest in black gaharu tea compared to yellow and green gaharu tea. This shows that fermentation process increased the amount of caffeine in gaharu tea leaves. Compared to market tea derived from leaves of Camillia sinensis, caffeine content in gaharu leaves is lower. Furthermore, the analysis of antioxidant was done using DPPH method. The result shows that antioxidant content is higher in fermented black and yellow gaharu tea compared to green gaharu tea. This shows that fermentation processed increased the antioxidant content in tea leaves. When comparing to standard commercial tea, gaharu tea has lower antioxidant content.